Cooperation Media Between PAI Teachers and Parents in Incorporating a Responsible Learning Attitude in Students at State Middle School 3 Sei Rampah - Wulandari, Widya; Hanum, Azizah (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2025)
Abstract This study aims to analyze the forms, obstacles, and solutions of media collaboration between Islamic Religious Education (PAI) teachers and parents in instilling a sense of responsibility for learning in students at SMP Negeri 3 Sei Rampah. Using descriptive qualitative methods, data was collected through observations, interviews, and documentation studies of PAI teachers, parents, and students. The results indicate that the collaborative media used included WhatsApp groups, letters, face-to-face meetings (POG), and mobile phone communication. Letters were considered effective in conveying information and motivating students, but success depended heavily on the active participation of parents. The main obstacles encountered were a lack of parental response due to busy schedules, limited access to technology, and low awareness of the importance of character education, including responsibility for learning. The solutions implemented included a variety of communication media, socialization of the importance of parents' roles, and regular face-to-face meetings. This study confirms that synergy and intensive communication between PAI teachers and parents through various media are key to successfully instilling a sense of responsibility for learning in students, while also significantly contributing to strengthening character education at school and in the family.Keywords: Media, Collaboration, Responsibility for Learning. AbstrakPenelitian ini bertujuan untuk menganalisis bentuk, hambatan, dan solusi kolaborasi media antara guru Pendidikan Agama Islam (PAI) dan orang tua dalam menanamkan rasa tanggung jawab belajar pada siswa di SMP Negeri 3 Sei Rampah. Dengan menggunakan metode kualitatif deskriptif, data dikumpulkan melalui observasi, wawancara, dan studi dokumentasi terhadap guru PAI, orang tua, dan siswa. Hasil penelitian menunjukkan bahwa media kolaborasi yang digunakan meliputi grup WhatsApp, surat, pertemuan tatap muka (POG), dan komunikasi telepon genggam. Surat dinilai efektif dalam menyampaikan informasi dan memotivasi siswa, tetapi keberhasilannya sangat bergantung pada partisipasi aktif orang tua. Kendala utama yang dihadapi adalah kurangnya respon orang tua karena jadwal yang padat, keterbatasan akses teknologi, dan rendahnya kesadaran akan pentingnya pendidikan karakter, termasuk tanggung jawab belajar. Solusi yang diterapkan meliputi media komunikasi yang bervariasi, sosialisasi pentingnya peran orang tua, dan pertemuan tatap muka secara berkala. Penelitian ini menegaskan bahwa sinergi dan komunikasi intensif antara guru PAI dan orang tua melalui berbagai media merupakan kunci keberhasilan dalam menanamkan rasa tanggung jawab belajar pada diri siswa, sekaligus memberikan kontribusi penting bagi penguatan pendidikan karakter di sekolah dan di keluarga.Kata Kunci: Media, Kolaborasi, Tanggung Jawab untuk Belajar.